Antifungal Effect of Silver Nitrate on Prosthodontic Dentures - Ozdogan Mahmut Sertac; Gumusok Mustafa; Yucel Mihriban; Dinc Bedia; Mizrak Muzaffer; Gungormus Mustafa (Balkan Journal of Dental Medicine, 2020)
Background/Aim: Although there are studies about the antimicrobial activity of silver, there is no study evaluating it as a denture disinfectant. The purpose of this study was to explore the effectiveness of 6 disinfectant solutions (50% vinegar, 100% vinegar, 1% silver nitrate, 2% silver nitrate, %1 sodium hypochlorite, 0,12% chlorhexidine digluconate) in the disinfection of acrylic resin specimens contaminated in vitro by Candida albicans, as measured by residual colony-forming unit (CFU).